On Freud's "On Beginning the Treatment" - Saragnano, Gennaro; Seulin, Christian (Contemporary Freud., 2012)
Like his other papers on technique, Freud's 1913 essay "On beginning the treatment" had an enduring influence on psychoanalysts for generations to come, providing them with a solid and worldwide-accepted conceptual basis on how to initiate psychoanalytic treatments. After a century of clinical experience and theoretical research, are all of Freud's rules and advice still valid today?Christian Seulin and Gennaro Saragnano have asked ten eminent analysts to comment upon this seminal paper of Freud's, each of them focusing on one of the fundamental issues originally propounded by the "father of page.